In-hospital neonatal maternal separation as early-life stress and neurodevelopmental disorders: a cross-sectional and population-based study - Quan Zhou; Quan Zhou; Senrui Liang; Yanyan Sun; Jun Fan; Zaisheng Qin (Frontiers in Psychiatry, 2025)
BackgroundNeurodevelopmental disorders are the most common psychiatric disorders in children and adolescents; however, preventing their onset and progression remains challenging. Due to ethical constraints, population-based studies investigating neonatal maternal separation (NMS) as an early-life stress in children and adolescents are scarce.MethodsWe analyzed data from five cycles (1999–2000 to 2007–2008) of the National Health and Nutrition Examination Survey, focusing on participants aged 1–15 years. The participants were identified using their replies to survey interview questions. The exposure of interest was in-hospital NMS, while the primary outcome was neurodevelopmental disorders, which include attention deficit hyperactivity disorder, learning disability, and special education or early intervention services. Multifactorial weighted logistic regressions with confounder adjustment were performed for participants with available data on the exposures, confounders, and outcome.ResultsOverall, data from 15502 participants (mean age, 8.05 years [SE 0.06]; 7759 males [weighted, 50.99%]) were analyzed. Neurodevelopmental disorders were more common in participants with prior experience of in-hospital NMS. Multifactorial weighted logistic regression model analyses revealed a significant positive association between in-hospital NMS and the occurrence risk of neurodevelopmental disorders (adjusted OR 1.82 [95% CI 1.40–2.37], P < 0.001). The pattern of association was largely consistent across the subgroups.ConclusionsIn-hospital NMS as an early-life stress is associated with an increased incidence of neurodevelopmental disorders in children and adolescents. This may be a targetable risk factor for future trials to examine the long-term outcomes of newborn-mother connection interventions and to tailor preventative and treatment interventions.